The next frontier: Moving human fear conditioning research online - Ney, Luke J.; O’Donohue, Matthew; Wang, Yi; Richardson, Mikaela; Vasarhelyi, Adam; Lipp, Ottmar V. (Biological psychology, 2023)
Fear conditioning is a significant area of research that has featured prominently among the topics published in Biological Psychology over the last 50 years. This work has greatly contributed to our understanding of human anxiety and stressor-related disorders. While mainly conducted in the laboratory, recently, there have been initial attempts to conduct fear conditioning experiments online, with around 10 studies published on the subject, primarily in the last two years. These studies have demonstrated the potential of online fear conditioning research, although challenges to ensure that this research meets the same methodological standards as in-person experimentation remain, despite recent progress. We expect that in the coming years new outcome measures will become available online including the measurement of eye-tracking, pupillometry and probe reaction time and that compliance monitoring will be improved. This exciting new approach opens new possibilities for large-scale data collection among hard-to-reach populations and has the potential to transform the future of fear conditioning research. •Fear conditioning is an important area of basic and applied research.•It is laboratory based which limits access to large and diverse samples.•Initial attempts to conduct fear conditioning online are limited to self-report.•Probe reaction time, eye movements and pupillometry offer alternative measurement options.